2019
DOI: 10.1186/s12879-019-4280-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous-to-oral antibiotic switch therapy: a cross-sectional study in critical care units

Abstract: Background This study aimed to evaluate the oral switch (OS) stewardship intervention in the intensive care unit (ICU). Methods This was a retrospective study with a convenience sample in two Brazilian ICUs from different hospitals in patients with sepsis receiving antibiotic therapy. The stewardship intervention included OS in patients diagnosed with sepsis when clinical stability was achieved. The primary outcome was overall mortality. Other variables evaluated were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 28 publications
2
29
0
2
Order By: Relevance
“…These ndings re ect the main diagnostic indications observed in this study, which referred to respiratory infections and septic shock. This data corroborates with several studies that point out the respiratory system as the most affected in ICUs [3,2,12,4]. When comparing the data from this study with others, it was found that the rate regarding the time spent using carbapenems was higher than the ndings by De Bus L et al [3] (236 DOT / 1000pd) and…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These ndings re ect the main diagnostic indications observed in this study, which referred to respiratory infections and septic shock. This data corroborates with several studies that point out the respiratory system as the most affected in ICUs [3,2,12,4]. When comparing the data from this study with others, it was found that the rate regarding the time spent using carbapenems was higher than the ndings by De Bus L et al [3] (236 DOT / 1000pd) and…”
Section: Resultssupporting
confidence: 91%
“…Similar data were observed by Rupali P et al [7] in which in the preintervention phase mortality was 22.4% and in the intervention phase 27.6%. Higher percentages were found by Marcelino FAB [2] (33.0%) and lower ones as described by De Bus L et al [3] (10.7%), Gasparetto J et al [12] (12.6%), and Álvarez-Lerma F et al [11], this reports that in the previous year the intervention the mortality percentage was 13.7% and in the following year after the intervention is reduced to 11.1%.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition to the antimicrobials described, studies still show expressive values of cephalosporin prescriptions in intensive care units [1-3, 6-8, 12]. These ndings corroborate with several studies that point out respiratory infections, followed by urinary infections, which explains the emphasis on cephalosporins, as the main predictors for the use of antimicrobials in ICUs [2][3][4]12].…”
Section: Discussionsupporting
confidence: 58%
“…However, for a large group of antibiotics it is proven that, if the circumstances are right, essentially the same amount of drug is found in the blood when given intravenously or orally [152]. The few studies that have investigated the bioequivalence, efficacy, and safety of an early IV-to-PO antibiotic switch in eligible adults ICU patients demonstrated a shorter ICU LOS, no increase in mortality, and lower costs of antibiotic therapy [153]. Nevertheless, we should remain cautious in critically ill patients, as was illustrated by anecdotal PK data on IV-to-PO switch of moxifloxacin in an adult ICU [154].…”
Section: Optimal Route: Intravenous To Oral Switch Therapymentioning
confidence: 99%